River journeys : a journey into the heart of Britain - Jones, Griff Rhys (Hodder & Stoughton, 2009)
Griff Rhys Jones, one of Britain's favourite travel presenters, explores the extraordinary rivers of Britain. Published to coincide with a major six-part series on BBC1.